LDL Receptor-related Proteinの動脈硬化巣での発現I: PCR法による検討 - 菊池, 正夫; 中村, 芳郎; 本間, 聡起; 清水, 健一郎; 中村, 隆一; 小宮山, 一雄; 石田, 浩之; 石山, 礼美子; 小薗, 康範; 広瀬, 信義 (動脈硬化, 1994)
LRP (LDL receptor-related protein) is considered to be one of the remnant receptors. Amino acid sequence analysis indicates that LRP is identical to the alpha2 macroglobulin receptor, which has been shown to bind and internalize following ligands; beta-VLDL with apoprotein E or lipoprotein lipase, alpha2 macroglobulin-protease complex, and plasminogen activator-inhibitor complexes. These characteristics indicate that LRP/alpha2 macro globulin receptor might be responsible in atherosclerotic lesions for foam-cell formation and regulation of protease activity. In order to investigate the role of LRP in atherogensis, we used the RT-PCR method to examine the expression of LRP mRNA in human atherosclerotic lesions.Atherosclerotic lesions were divided into three groups: normal intima, raised lesion, and calcified lesions. From these fractions, total RNA were extracted by the AGPC method and RT-PCR was performed.The results of PCR showed that expression of LRP mRNA was more abundant in atherosclerotic lesions than in normal intima or media, suggesting that LRP might play a role in atherosclerosis.